Low power reconfigurable sub-band filter bank ASIC for MP3 decoder - Gangamamba, B. P.; Muralidhar, P.; Murthy, N. S. (Inderscience Enterprises Limited, 2009)
Link to publisher's homepage at http://inderscience.com/